Propuesta de un plan estratégico de marketing para El Laboratorio Médicos, de la ciudad de Loja - Suing Bailón, Letty Paola (2014)
The aim of this research is to present a proposal of strategic marketing plan for Laboratory Medico, a private company being run by its owner and oriented on provision of clinical laboratory services, which since its inception has noted some significant growth and changes, mainly due to the increase of regular patients and implemented technological improvements. There are two main services provided by the laboratory: i) the exams are made for on-site patients of the laboratory; and ii) for other small laboratories. The proposal of strategic marketing plan contains the strategic and operational guidelines for the next three years, aligning strategically the mission, vision and values with real action plans, especially executable plans. There was a survey carried out and applied to customers and employees of the laboratory, as well as to laboratories that have a service agreement with that laboratory. There was done an interview with the owner of the laboratory; and the results obtained helped identify the level of satisfaction of internal and external customers. In addition, a survey was held to define the vision, mission, values, target market, business services, FODA and generic strategy. This study begins with a brief training on the general concepts related to strategic planning and marketing, then it analyzes the information related to the environment in which the laboratory arranges its services. In this part there are defined as well as the mission, vision and values. For the FODA analysis, there were formed working groups based on two business services mentioned previously. There was also established an outline of the possible strategies. The formulation of strategies were following: generic and specific strategic impact analysis, prioritization of projects, budgets, action plans and results forecast were made in a particular way with the director manager. The strategic objectives were to increase the profitability of the laboratory, its participation on the market on local level, to improve and develop customer service, to promote and offer competitive services. In order to implement all action plans included in the proposed strategic marketing plan, there is a need of increasing the profitability of the laboratory, improving and developing customer service, promotion and provision of competitive services, regulating all internal processes and providing a better organization of services. Key words: Strategic marketing plan, Laboratory Medico, technological improvements, strategic and operational guidelines, mission, vision and values, results forecast, profitability, customer service According to the results obtained it can be concluded that it is necessary to:  Increase the profiability of the laboratory. To fulfill this objective, an investment of $1.700 is required.  Increase the participation of the laboratory in the market. There is required an investment of $ 30.200 in order to achive this objetive.  To promote and offer competitive service, that would need to count with an investment of $ 3.400.  Impove and develop custmer service and for this would be need an investment of $35.750. The estimated Budget of the next strategic plan in order to achive all objectives mentioned above is in total $ 71.050